Caso de estudio: Empresa Overall - Alvarado Coello, Sebastian (2022)
This work will be based on Executive Solutions S.A., a business unit of Corporativo Overall dedicated to the outsourcing of industrial services with an annual turnover of more than S/. 30 million. It will also focus on three of its main clients: Softys (Protisa S.A.), Trupal S.A. and Quimpac S.A. Outsourcing in Peru has helped to formalize a greater number of workers, giving them all the benefits of the law. In addition, it is beneficial for the company that hires the services because it focuses mainly on the core business and on allowing them to grow, so that secondary activities do not interfere with the proposed goals. The purpose is to indicate strategic objectives to be achieved in the following years through a deep analysis of the external and internal level of the sector, also evaluating strategic planning matrices that will help to identify the strategy to follow.